Antifungal molecular details of MNQ-derived novel carbon dots against Penicillium digitatum. (1st July 2023) - Liu, Yongchun; Li, Wei; Wu, Keyue; Lei, Bingfu; Chen, Jianying; Zhang, Xiaoyong; Lei, Hongtao; Duan, Xuewu; Huang, Riming
Graphical abstract: Highlights: Application of natural compounds for biological control of postharvest diseases. MNQ-CDs synthesized through a solvothermal route were used as antifungal agents. A combined multi-omics analysis of the antifungal mechanism was used. Abstract: It is urgent to develop high-efficiency and low-toxicity natural antifungal agents on green mold caused by Penicillium digitatum . The effect of 2-methoxy-1, 4-naphthoquinone (MNQ) inhibition of P. digitatum was not very satisfactory. MNQ-derived carbon dots (MNQ-CDs) synthesized through a solvothermal route were used as antifungal agents against P. digitatum . The antifungal activity of prepared MNQ-CDswas enhanced compared to MNQ, and the minimum inhibitory concentration was 2.8 μg/mL. A total of 441 genes and 122 metabolites have undergone significant changes. The omics data revealed that MNQ-CDs primarily modified the metabolism of aromatic amino acids and synthesis of the cell membrane in P. digitatum, thereby inhibiting its propagation. Furthermore, compared with MNQ, MNQ-CDs had a better control effect on the green mold of citrus fruits, and could more significantly inhibit the propagation of P. digitatum . This study provides a new idea for the design of new and efficient antifungal materials.